2021
DOI: 10.1016/j.ijid.2021.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Transmitted drug resistance among HIV-1 drug-naïve patients in Greece

Abstract: Objectives: Despite the success of antiretroviral treatment (ART), the persisting transmitted drug resistance (TDR) and HIV genetic heterogeneity affect the efficacy of treatment. This study explored the prevalence of TDR among ART-naïve HIV patients in Greece during the period 2016-2019. Methods: Genotypic resistance testing was available for 438 ART-naïve HIV patients. Multivariable Poisson regression models were fitted. Results: The majority of patients were male, and there was a slight predominance of Hell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…To our knowledge, this is the most updated study showing transmitted resistance to ARV in Spain 14–22 . SDRM detection, in our study, was in line with recent studies published worldwide 18,23–26 with ours again being one of the studies presenting data from a most recent calendar period.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this is the most updated study showing transmitted resistance to ARV in Spain 14–22 . SDRM detection, in our study, was in line with recent studies published worldwide 18,23–26 with ours again being one of the studies presenting data from a most recent calendar period.…”
Section: Discussionsupporting
confidence: 91%
“…Although the current WHO survey methodology is not designed to distinguish between PDR and TDR and incidence test are seldomly used in HIVDR prevalence studies or surveys, some studies reported an initial rise in TDR especially to NNRTI which declined possibly due to policy changes involving transition to well-tolerated and high genetic barrier drugs such as DTG-based ART [13][14][15][16][17][18]. On the other hand, the prevalence of TDR to INSTIs is still very low [18,19 & ,20-22].…”
Section: Andandmentioning
confidence: 99%
“…). The proportion of countries meeting the target of having at least 5% of patients on secondline ART increased from 45% (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) in 2017 to 56% (14 of 25) in 2020. Overall, most countries reported sub-optimal performance in preventing HIVDR, indicating the need to strengthen the quality and monitoring systems and implement sustainable solutions.…”
mentioning
confidence: 99%
“…Transmitted drug resistance (TDR) of HIV is prevalent but varies worldwide. For example, the prevalence of TDR of HIV has been reported to be 4.1% in south/southeast Asia and 6.0% in sub-Saharan Africa [ 6 ] 14% in southwestern Siberia [ 7 ], 7.8% in Greece [ 8 ], 8.0% in Brighton [ 9 ], and 13.1% in Portugal [ 10 ]. In 2015, a nationwide cross-sectional survey revealed that the overall prevalence of TDR was 3.6% in China [ 11 ].…”
Section: Introductionmentioning
confidence: 99%